The Influence of QR Code-Based Socialization on Passenger Understanding of KM 39/2024 Regulations at Komodo International Airport - Putri Pratitis, Anggid; Rochmawati, Laila; Purwayudhaningsari, Ranatika (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
The Minister of Transportation's Decree Number 39 of 2024 serves as an important reference in maintaining flight safety. However, there are still many violations by passengers regarding cabin baggage, reflecting a lack of understanding of regulations and minimal information dissemination. Digital media such as QR Codes are considered an efficient solution for delivering information. This research uses a quantitative approach involving 233 domestic passengers at Komodo International Airport. A questionnaire was developed to measure the influence of QR Code media on passengers' understanding of KM 39 of 2024, with instruments that have been validated and tested statistically. The analysis results show that QR Code has a significant impact on improving passenger understanding (p < 0.05). The recommended strategies based on PM 30 of 2020 and PM 77 of 2011 include placing QR Codes in strategic locations, presenting engaging content, and involving staff in assisting passengers to access information digitally in accordance with service regulations and carrier responsibilities.